2013
DOI: 10.1371/journal.pone.0065358
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of Peptides LVEALYL and RGFFYT and Their Binding Affinity to Insulin

Abstract: Recently it has been proposed a model for fibrils of human insulin in which the fibril growth proceeds via stacking LVEALYL (fragment 11–17 from chain B of insulin) into pairs of tightly interdigitated -sheets. The experiments have also shown that LVEALYL has high propensity to self-assembly and binding to insulin. This necessitates study of oligomerization of LVEALYL and its binding affinity to full-length insulin. Using the all-atom simulations with Gromos96 43a1 force field and explicit water it is shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
1
18
1
Order By: Relevance
“…Region-IV hydrophobic residues are prominently solvent exposed in the PF2 (B20 Gly, B23 Gly, B24 Phe) and the PF3 (B20 Gly, B24 Phe, B25 Phe, B26 Tyr) states. These residues are part of the RGFFYT segment speculated to modulate the insulin fibril growth process (130). In contrast, we find that a maximum of only two hydrophobic residues are solvent exposed from regions I or II in any of the PF-states, indicating these regions could be less important in contributing to early stages of insulin aggregation process.…”
Section: Partially Folded Statescontrasting
confidence: 56%
See 2 more Smart Citations
“…Region-IV hydrophobic residues are prominently solvent exposed in the PF2 (B20 Gly, B23 Gly, B24 Phe) and the PF3 (B20 Gly, B24 Phe, B25 Phe, B26 Tyr) states. These residues are part of the RGFFYT segment speculated to modulate the insulin fibril growth process (130). In contrast, we find that a maximum of only two hydrophobic residues are solvent exposed from regions I or II in any of the PF-states, indicating these regions could be less important in contributing to early stages of insulin aggregation process.…”
Section: Partially Folded Statescontrasting
confidence: 56%
“…Regions I and III have been shown to play a crucial role in the insulin fibrillation process by both aggregation incubation experiments and molecular simulations (110,118,(126)(127)(128)(129). Recently, an MD study showed that peptides from regions III and IV show similar oligomerization propensity and similar binding affinity to native insulin (130). We find the most significant exposure of hydrophobic residues in regions III and IV.…”
Section: Partially Folded Statesmentioning
confidence: 58%
See 1 more Smart Citation
“…12 Such improperly exposed peptide sequences, especially those including the central B-chain helix LVEALYL, are thought to be aggregation prone/amyloidogenic 13 and can associate with neighboring insulin moieties, even when they are in the native state. 14 In the native state, two of the insulin disulfide bonds-C(A6)-C(A11) and C(B19)-C(A20)-are no longer exposed to solvent, and both burying and consumption of the C(A11) thiol are particularly important for the proinsulin folding pathway. 15 In beta cells, proinsulin synthesis begins as preproinsulin polyribosomes dock at the ER membrane such that the nascent translation product is translocated into the ER lumen, followed by cleavage of its signal peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Structural polymorphism probably leads to various surface patterns having different intra-or inter-residue arrangements [78]. Chiang et al suggested that, in addition to the B11-B17 fragment, the B22-B27 sequence can also modulate fibril growth [79]. In terms of finding the smallest amyloidogenic sequence, Swiontek et al showed that the shortest components of A13-A19, B12- B17 fragments, which contained the amino acid residues H-LeuTyr-OH (A13-A14) and H-TyrLeu-OH (B16-B17), were able to form fibrils [19].…”
Section: Discussionmentioning
confidence: 99%